Effects of Hexane Addition in Waste Plastic Fuel-Biodiesel-Diesel Blends on the Performance and Emission Characteristics of DI Diesel Engine - Rajan Kumar; Manoj Kumar Mishra; Manish Kumar Roy (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2022)
The current study's sole objective is to evaluate the impact of hexane's addition to blends of diesel, waste plastic fuel, and jatropha biodiesel. Five fuel samples have been made in order to do this, including diesel-waste plastic fuel-jatropha biodiesel (D70WPF20JB10 and D70WPF10JB20), diesel-hexane-waste plastic fuel-jatropha biodiesel (D65HX5WPF20JB10 and D65HX5WPF10JB20), and plain diesel (D100) as a reference fuel. Following thorough characterization, studies using spectroscopic techniques such as FTIR, elemental analysis, and GC-MS are conducted. Finally, performance and emission tests on a direct-injection single-cylinder diesel engine were conducted. The density, flash point, and acid value of the diesel-waste plastic fuel-jatropha biodiesel blend are observed to decrease with the addition of hexane. With the addition of hexane, the calorific value and diesel index of the fuel both rise by 0.86% and 12.5%, respectively. In the case of the hexane mix fuel samples, it is discovered that the brake thermal efficiency and volumetric efficiency are higher and the brake-specific fuel consumption is lower. Hexane is added to the diesel-waste plastic fuel-jatropha biodiesel mixture, which results in a 34 percent rise in HC emissions and a 9 percent decrease in CO emissions. Additionally, it lowers by 8% and 15%, respectively, the temperature of the exhaust gas and the fuel's NOx emissions. The fuel sample with code D65HX5WPF10JB20 exhibits the best results among all the fuel samples in terms of performance and emission analyses.